Simplistic approach for in situ generation of ZnS quantum dots in polyphenylene sulphide matrix via chalcogen enriched solid–solid reaction technique. Issue 2 (26th November 2012) - Rumale, Narendra; Arbuj, Sudhir; Umarji, Govind; Shinde, Manish; Mulik, Uttam; Pokle, Anuj; Amalnerkar, Dinesh
Abstract Herein, we report in situ synthesis of zinc sulphide (ZnS) quantum dots in polyphenylene sulphide (PPS) matrix employing facile solid–solid reaction. The resultant product reveals formation of cubic nanocrystalline zinc sulphide structure. The HRTEM confirms the formation of zinc sulphide quantum dots (size ∼ 3–4 nm) embedded in the polymer matrix. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Scheme: ZnS QDs by enriched solid–solid reaction in polymer matrix.